Analysis of the Solidification Process of Metal Alloys Under Microgravity Conditions - Fredriksson, Hasse (Frontiers in Metals and Alloys, 2022)
The solidification of metal alloys under low gravity conditions mainly deviates in four physical properties compared with samples solidified on earth. The coarseness of the structure and the solidification temperature increase. The latent heat and the solubility of alloying elements in solids are changed. Experimental results are presented and analyzed in order to find a unified theoretical understanding. The differences in the measured quantities between experiments performed in space and on earth were calculated and are presented in this article. Kinetic, thermodynamic, and thermophysical relations were used to analyze those values. The change in the melting point was found to be a result of an increase in the vibrational amplitude of the atoms in the solid. The increase in the latent heat results from an increase in the vibration of atoms in the liquid. The changes in the solubility are a result of an increase in heat of fusion of the alloying element. Furthermore, the increase in the coarseness of the structure is explained as an increase in the atom’s vibration. The analysis highlights that the atom’s vibration increases with decreasing gravity; especially, the amplitude will increase. The explanation for this is given by a decrease in the binding energy between the atoms with decreasing gravity. The decrease in binding energy for liquids is larger than for solids.